ON ROUGH APPROXIMATIONS OF SUBGROUPS VIA CONJUGACY - Kumar, V. Srinivasa; Reddy, Y. Madhavi (Italian Journal of Pure and Applied Mathematics, 2015)
Conjugacy is a very significant equivalence relation in the theory of groups and it has several important applications as well. In this present paper, we use this equivalence relation to generate Rough sets. A few results are presented in this context by assigning a group structure to the universe set. Some interesting properties of Lower and Upper approximations of subgroups are investigated.